Efficient alkaloid capture from water using a charged porous organic polymer. Issue 58 (27th September 2018) - Zhang, Qing-Mei; Wang, Zhen; Cheng, Guang; Ma, Hui; Zhang, Qing-Pu; Wan, Fu-Xian; Tan, Bien; Zhang, Chun
Abstract : A charged porous polymer displays excellent adsorption capacity for berberine hydrochloride from the synergistic effects of size matching and electrostatic interaction. Abstract : Berberine hydrochloride (BH), an important alkaloid, can be captured from water and released in organic solution circularly by a charged porous polymer (TPB–HCP), which is hypercross-linked using the cost-effective Friedel–Crafts reaction using sodium tetraphenylborate as the monomer. With high BET surface area, hierarchical porous structure and charged characteristics, TPB–HCP displays excellent adsorption capacity for BH owing to the synergistic effects of size matching and electrostatic interaction.